Revision of the family Carabodidae (Acari: Oribatida) XVI. Synkrotima tsalakpmenoi sp. nov. from Zimbabwe and Kenya, and Congocepheus thailandae sp. nov. from Thailand, including a complementary study of Cavaecarabodes hauseri (Mahunka 1989) - Fernandez, Nestor; Theron, Pieter; Leiva, Sergio; Jordaan, Anine (Zootaxa, 2018)
Synkrotima tsalakpmenoi sp. nov. is described from material collected in Zimbabwe and Kenya. This species presents the following characteristics: notogastral integument formed by longitudinally aligned cuticular cords; thick, lanceolate notogastral setae; and genital neotrichy. Synkrotima tsalakpmenoi sp. nov. is compared to S. zimbabwae. Congocepheus thailandae sp. nov. is the first species of this genus described from Thailand, with the following present: large finger-like notogastral projection; notogastral setae c1, c2, da, dm, dp, la, lm, lp, h1, h2 situated on promontories; setae c1, c2 located adjacent and parallel.        A complementary study of Cavaecarabodes hauseri, making use of Scanning Electron Microscopy (SEM), allows for clarification of particularities regarding complex setae as well as some aspects of the integument, and provides a more detailed diagnosis.